Sharp injuries in clinical practice among nursing students of Da Nang University of Medical Technology and Pharmacy - Nguyen, Trinh Thi Doan; Hoang, Hoa Thi Minh; Luong, Dieu Thi Hien (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: While studying at the hospital, nursing students are at risk of getting sharp instrument injuries during clinical practice. The likelihood of being injured by sharp instruments in nursing students is very high due to prolonged clinical practice in medical facilities, working in new environments, lacking experience, and concentration. Our study aimed to detect the prevalence of students injuring themselves with sharp instruments in clinical practice and the related factors influencing this rate. Methods: A descriptive cross-sectional study was conducted on 400 nursing students going for clinical practice from January 2018 to May 2018 at Da Nang University of Medical Technology and Pharmacy. Data were collected through self-filled questionnaires. Results: Our study showed that 71% of students were hurt by sharp instruments. The number of injuries, including 1 time, 2 times, 3 times, and more than 3 times, accounted for 14.8%, 18.7%, 19.7%, and 46.8%, respectively. Fingers were the most frequently damaged position (74.7% of the total number of injured cases), followed by hands (22.9%), toes (1.5%), and feet (0.9%). The Faculty of Internal Medicine (42.8%) was the most common place of occurrence, followed by the Department of Surgery (32.8%), Rehabilitation Department (8.6%), Department of Pediatrics (7.9%), and Emergency Department (7.9%). Significant relationships were found between the proportion of sharp instrument injuries and students’ learning ranking, training on using sharp instruments safely, and students’ knowledge about sharp instruments (p<0.05). Conclusions: The proportion of nursing students injured by sharp instruments was significantly high and associated with students’ learning ranking, training about sharp instrument safety, and qualified knowledge about sharp instruments.